Категорія «Музичні інструменти» в свідомості носіїв англійської мови - Хаджиоглова, Олена Георгіївна; Khadzhyohlova, Olena (Запоріжжя : ЗНУ, 2012)
У статті розглядаються результати психолінгвістичного експерименту, проведеного з носіями англійської мови. Експеримент був скерований на виявлення структури категорії «музичні інструменти». The article is aimed at description of the results of a psycholinguistic experiment that was conducted with the English-speaking people. The main idea of the experiment was to discover the structure of the “musical instruments” category.
Category “musical instruments” in the consciousness of English-speaking people
Keywords: категоризація, категорія, ядро, прототип, периферія; categorization, category, nucleus, prototype, periphery